INTERNALISASI NILAI RELIGIUS MELALUI TRADISI PANGKU PALIARE PADA ANAK USIA DINI - Maudi, Maudilia Septianti D.Y.P; Rudiyanto; Asep Deni Gustian; Andika Pradana Putra (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2025)
This research aims to describe the implementation of the Pangku Paliare tradition in Muara Dua Village, Bengkulu Province, as well as to identify the religious values contained within and their role in internalizing values for early childhood. Pangku Paliare is an annual tradition held every 1st of Muharram as a form of gratitude to God for safety and sustenance. This tradition involves the entire community, including children, who participate in various customary activities as a means of teaching life and spiritual values. The researcher employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model by Miles and Huberman through the stages of data reduction, presentation, and conclusion drawing. The results indicate that this tradition has three main stages: preparation, the main event, and closing, all of which are rich in religious and social values. Values such as honesty are reflected in elders' advice; gratitude is expressed through communal prayers on the 10th of Muharram; and mutual cooperation and togetherness are evident in activities preparing for the Mlemang procession. The involvement of children in all series of activities makes this tradition an effective medium for character education based on local wisdom.